Program Asimilasi Dan Integrasi Kepada Anak Didik Pemasyarakatan Saat Pandemi Covid-19 (Studi Kasus di Lembaga Pembinaan Khusus Anak Kelas I Kutoarjo) - Rizqi Mely Trimiyati; Mitro Subroto (Faculty of Law, Diponegoro University, 2022)
Efforts tried by the Indonesian government in carrying out the handling of Covid-19 widely. As one of the implementations that are being tried to prevent the formation of the spread of Covid-19, which is being tried by the Child Special Guidance Agency (LPKA). The issuance of the Regulation of the Minister of Law and Human Rights Number 43 of 2021 concerning the Second Substitution of the Minister of Law and Human Rights Number 32 of 2020 concerning Provisions and Methods for Providing Assimilation, Conditional Release, Leave Before Liability and Conditional Leave for Convicts and Children in the Context of Deterring and Overcoming the Spread of Covid-19. The issuance of regulations This creates pros and cons between the community. In this case, people are worried about the increase in the crime rate. The implementation of Minister of Law and Human Rights Number 43 of 2021 at the Kutoarjo Class I Children's Special Guidance Institute as many as 9 correctional students as of January 2022, in its implementation has negative and positive consequences. The provision of assimilation and integration programs at the Kutoarjo Class I Children's Special Guidance Institute has succeeded in reducing overcrowding, saving pay and increasing children's productivity. Keywords: Assimilation; Integration; Correctional Students Abstrak Upaya yang dicoba oleh pemerintah Indonesia dalam melaksanakan penanggulangan Covid- 19 secara meluas. Selaku salah satu implementasi yang dicoba buat melaksanakan penangkalan terbentuknya penyebaran Covid- 19 yang dicoba oleh Lembaga Pembinaan Khusus Anak (LPKA). Dikeluarkannya peraturan Permenkumham Nomor 43 Tahun 2021 Tentang Perubahan Kedua Atas Permenkumham Nomor 32 Tahun 2020 Tentang Ketentuan Serta Tata Cara Pemberian Asimilasi, Pembebasan Bersyarat, Cuti Menjelang Bebas Serta Cuti Bersyarat Untuk Narapidana Serta Anak Dalam Rangka Penangkalan Serta Penanggulangan Penyebaran Covid- 19. Adanya dikeluarkannya peraturan tersebut mengakitabkan pro dan kontra diantara masyarakat. Dimanya masyarakat timbul rasa khawair akan meningkatnya angka kriminalitas. Pelakasnaan Permenkumham Nomor 43 Tahun 2021 di Lembaga Pembinaan Khusus Anak Kelas I Kutoarjo sebanyak 9 anak didik pemasyarakatan per Januari 2022, dalam pelaksanaannya mempunyai akibat negatif dan positif yang ditimbulkan tersebut. Pemberian program asimilasi serta integrasi di Lembaga Pembinaan Khusus Anak Kelas I Kutoarjo, sukses kurangi kepadatan, mengirit bayaran dan tingkatkan produktivitas anak. Kata Kunci: Asimilasi; Integrasi; Anak Didik Pemasyarakatan